Creation of the scientific and educational laboratory for nanotechnologies is a necessary step in this area (Pedagogy of Higher and Secondary Education, 2016)
Lukashenko T. F, Kushchevskaya N. F, Malyshev V. V. Creation of the scientific and educational laboratory for nanotechnologies is a necessary step in this area.Nowadays, the implementation in higher educational institutions a new qualification program of training nanotech industry, which is the synthesis of scientific fields such as physics, chemistry, biology, and mathematics is of current interest.The purpose of the present work is to highlight the creation of scientific and educational nanotechnology laboratories within the higher educational institutions, to set goals and objectives of their activities, to find sources for their funding and logistical support, and to introduce the special course «Nanotechnology basics». Scientific and Education Nanotechnology Laboratory (SENL) is the scientific structural department of the Institute of Engineering & Technology of the University «Ukraine» aimed to solve urgent fundamental, applied, scientific, and educational problems in the field of nanotechnology having high relevance and educational value. SENL is created to unite and coordinate the efforts of departments of the University «Ukraine», of the institutions of the NAS of Ukraine, of sectoral research institutes, and of companies aimed at scientific and educational activities in the field of nanotechnology and nanosystems sciences.The SENL purpose is the provision of high-quality training of school teachers and highly qualified specialists in the field of nanosystems, nanomaterials, and nanotechnologies based on: integration of scientific and pedagogical potential of departments of the University «Ukraine» in implementing fundamental and applied scientific researches; commercialization of their results; development of new programs and methods developing and combining fundamental research and educational process; methodical support of educational process; development of international cooperation.The article is devoted to the training of engineers in the field of nanotechnologies with application of new promising scientific developments. Attention is drawn to the need for scientific and educational laboratory for nanotechnologies. The functioning of such laboratory within the structure of the Engineering & Technology Institute of the University «Ukraine» is discussed; goals and objectives of its work have been defined.
Keywords: ngineering personal; nanotechnologies; scientific educational laboratory; educational activities; special course «Nanotechnologies Basics»; nanosciences; nanotech industry